Enhanced depth imaging optical coherence tomography of choroidal osteoma with secondary neovascular membranes: report of two cases - Mello,Patrícia Correa de (2016)
ABSTRACT We report enhanced depth imaging optical coherence tomography (EDI-OCT) features based on clinical and imaging data from two newly diagnosed cases of choroidal osteoma presenting with recent visual loss secondary to choroidal neovascular membranes. The features described in the two cases, compression of the choriocapillaris and disorganization of the medium and large vessel layers, are consistent with those of previous reports. We noticed a sponge-like pattern previously reported, but it was subtle. Both lesions had multiple intralesional layers and a typical intrinsic transparency with visibility of the sclerochoroidal junction.